ARAHAN PENANGANAN KAWASAN PERMUKIMAN KUMUH DI DESA WANI 1 KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Rizkhi, Rizkhi; Saleh, Amanda Wiranti; Akhmad, Abdul Gani (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Slum settlements remain a major issue in Donggala Regency. This includes residential areas with high economic potential but numerous environmental problems, such as in Wani 1 Village, Tanantovea District. The government’s handling efforts have not yet fully resolved the livability issues in the area. Therefore, this study aims to conduct a deeper assessment of settlement problems to formulate handling guidelines based on the conditions and levels of slum severity in Wani 1 Village. These guidelines are expected to serve as a reference for optimizing government efforts in addressing slum settlement problems. The research method used is quantitative with a descriptive approach. Based on the analysis and calculations, Wani 1 Village falls into the categories of moderate and light slum areas. The reduction in slum levels has been driven by government intervention programs initiated in 2017. This indicates an improvement in the quality of the area, particularly in basic infrastructure aspects such as the construction of neighborhood roads, drainage systems, individual sanitation facilities, and the provision of clean water. However, the handling efforts have not yet been fully optimized, as several unresolved issues remain. Therefore, the recommended handling direction for Wani 1 Village is to improve the quality of problematic aspects based on existing conditions, in order to organize and rehabilitate the area toward creating livable and non-slum settlements.